An Intellectual Legacy: Chalilakath Kunjahammed Haji’s Role in Modernizing Madrasa Education - Ibrahim Badhusha Parakkallil (Al-Fadlan: Journal of Islamic Education and Teaching, 2025)
The paper analyzes the development and modern features of Religious Education particularly Islamic Education in Kerala paying considerable attention to the pioneer Chalilakath Kunjahammad Haji in changing Islamic Education system in Malabar. The study also explores the roots of religious education in Kerala and findings methods in practice for a long time from a traditional method called dars pre-scheduling an important knowledge about religion to Muslim community. In such a context, the research explores if and how Haji has tried to change his practices and introduce new methods of education and teaching/learning practices such as curriculum teaching, examination system, classroom teaching learning inspired by the more advanced system of education like Bakhiatul Swalihat in Vellore. The former domain of Haji shows an important future of secular sciences with religious education, where in inserted astronomy and mathematics, became a specialization of knowledge in madrasas of Kerala. The paper also situates Haji aim and struggle towards putting the plan of education reform in the context of sociopolitical context of the Malabar in the century end that received him both the support and opposition for his measures towards modernizing the Muslim education. The paper also explores a significant period in Haji’s life, namely the invitation to reinvent theeducational institutions with the support of such civic patrons as Koyappathodi Ahmed Kutti Haji based on cooperation principles. Finally, being one of the most important theological controversies, Ainul Qibla Debate prompts the consideration of the correlation between theology and progressive/sustainable educational development in Kerala; it also demonstrates how contributive Haji’s thoughts have been to the creation of the progressive but at the same time traditional model of Islamic schooling. This research helps to fill the gap in the literature regarding religious reform and the ways scholars navigated between the poles of change and tradition in the implementation of the Islamic education.